Розроблення ароматичних композицій з ефірної олії шавлії мускатної для інкапсулювання гуміарабіком - Чепель, Наталія Василівна (My University, 2014)
Розроблення ароматичних композицій з ефірної олії шавлії мускатної для інкапсулювання гуміарабіком При розроблені ароматичних композицій з ефірної олії шавлії мускатної (Salvia sclarea) для інкапсулювання гуміарабіком проводили визначення динаміки адсорбції органічних класів ароматичних речовин та розділення ефірної олії на заплановані фракції з відмінними ароматичними властивостями вакуумною ректифікацією. Для встановлення масових співвідношень фракцій у ароматичних композиціях застосовували симплекс-метод математичного моделювання. Development of aromatic compositions from salvia sclarea essential oil for encapsulation by gum arabic This article presents the development of aromatic compositions from Salvia sclarea essential oil for their encapsulation depending on the adsorption properties of gum arabic with regard to organic classes of aromatic compounds. The dynamics of aromatic compounds adsorption in applying the gum arabic has shown the low selectivity for the organic class of terpenes and the high selectivity for the organic classеs of oxygen derivatives of terpenes. The separation of Salvia sclarea essential oil into its fractions with the low terpenes content and the difference of aromatic properties were performed by vacuum rectification using the complex approach. The mathematical modeling for the development of aromatic compositions from Salvia sclarea essential oil was used. The development of aromatic compositions from Salvia sclarea essential oil depending on the adsorption properties of gum arabic has allowed to find out the mass ratios of its fractions for the aromatic composition "Sweet Sage" – 2fraction: 3fraction: 4fraction =1.34 – 1.45: 2.05-2.15: 86.32 – 86.76: 3.78 – 4.98 and for the aromatic composition "Muscat Harmony" - 2fraction: 3fraction: 4fraction =0.76 – 0.81: 10.78 – 10.85: 17.43 – 17.56: 43.22 – 43.67. The first fraction of Salvia sclarea essential oil with high terpenes content has not been used in the development of aromatic compositions.
Keywords: ефірна олія шавлії; sage essential oil; гуміарабік; gum arabic; ароматизатор; flavouring; кафедра технології молока і молочних продуктів